Pengaruh Social Media Marketing, Destination Image, Dan Destination Branding Terhadap Minat Berkunjung Di Santera De Laponte Pandesari Kec. Pujon Kab. Malang - Azzahra, Intan Nirwana; Asiyah, Siti; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study's goal is to analyze the effects of social media, pariwisata, and destination branding on travelers' desire to visit the Pandasari in Pujon, Malang. Using the purposive sampling technique, which is based on a sample size of at least 60 respondents, the population in this study is the people of Kabupaten Malang. Two types of sumber data are used: primary and secondary data. technique for gathering data by providing information to the public. SPSS version 25 is used as an analytical tool in the methodology of data analysis. The study concludes that social media marketing, destination branding, and tourism tourism all have an impact on travelers' desire to visit simultaneously. However, Pemasaran Media Sosial does not have any significant dampak against berkunjung minat, Citra Destinasi does not have any significant dampak against berkunjung minat, and Destination Branding does not have any significant dampak against.  Keywords: Social Media Marketing, Destination Image, Destination Branding, Interest in Visiting